Fourth-Generation Analogues of the Anticancer Peptaibol Culicinin D: Probing the Effects of Hydrophobicity and Halogenation on Cytotoxicity - Kasim, Johanes K.; Kavianinia, Iman; Bull, Matthew; Harris, Paul W. R.; Smaill, Jeff B.; Patterson, Adam V.; Brimble, Margaret A. (Synthesis, 2021)
Preliminary results of the effect of hydrophobicity and halogenation on the cytotoxicity of the anticancer peptaibol culicinin D are reported. Building on previous work, the synthetically challenging (2S,4S,6R)-2-amino-6-hydroxy-4-methyl-8-oxodecanoic acid and (2S,4R)-2-amino-4-methyldecanoic acid building blocks were replaced with derivatives of l-phenylalanine and 2-aminodecanoic acid, respectively. Substitution of (2S,4S,6R)-2-amino-6-hydroxy-4-methyl-8-oxodecanoic acid with l-4,4′-biphenylalanine yielded an analogue that was tenfold more potent than the natural product and was also the most hydrophobic analogue, as judged by an antiproliferative IC50 assay and logD calculations; these results suggest that the potency of culicinin D may be governed by its hydrophobicity. However, the introduction of halogenated moieties into the peptide sequence generated analogues that were similarly potent, although not necessarily hydrophobic. Thus, the parameters regulating the cytotoxicity of culicinin D, and by extension other peptaibols, are multimodal and include both halogenation and hydrophobicity.
Keywords: anticancer compounds; peptides; peptaibols; culicinin D; hydrophobicity; halogenation; cytotoxicity